Current hotspots and trends in cancer metabolic reprogramming: a scientometric analysis - Yang, Shanshan; Lin, Miaomiao; Hao, Shaodong (Frontiers in Immunology, 2024)
BackgroundMetabolic reprogramming (MR) in cancer (CA) has been a focus of intense research in the recent two decades. This phenomenon has attracted great interest because it offers potential targets for cancer therapy. To capture the intellectual landscape of this field, we conducted a bibliometric analysis to assess the scientific output, major contributors, and trends in the MR/CA research.MethodsWe performed a systematic search using the Web of Science to retrieve articles published on MR of cancer from 2006 until 2023. The bibliometric tools such as Biblioshiny, VOSviewer, and Microsoft Excel were used to identify the most prolific authors, institutions, citation patterns, and keywords. We also used co-citation analysis to map the conceptual structure of the field and identify influential publications. Furthermore, we examined the literature by analyzing publication years, citations, and research impact factors.ResultsA total of 4,465 publications about MR/CA were retrieved. Publications on MR/CA increased rapidly from 2006 to 2023. Frontiers in Oncology published the most papers, while Cell Metabolism had the most citations. Highly cited papers were mainly published in Cancer Cell, Nature, Cell, Science and Cell Metabolism. China and the United States led the way in publications and contributed the most to MR/CA research. The University of Texas System, Chinese Academy of Sciences, and Fudan University were the most productive institutions. The profitable authors were Deberardinis Ralph J and Chiarugi Paola. The current topics included MR in tumorigenesis and progression of CA, MR of tumor cells and tumor microenvironment, the effect of MR on the CA treatment, the underlying mechanisms of MR (such as gene regulation, epigenetics, extracellular vesicles, and gut microbiota), and the modulation of MR. Some topics such as tumor microenvironment, lipid MR, circular RNA, long noncoding RNA, exosome, prognostic model, and immunotherapy may be the focus of MR/CA research in the next few years.ConclusionThis study evaluated the global scientific output in the field of MR/CA research, analyzing its quantitative characteristics. It identified some significant and distinguished papers and compiled information regarding the current status and evolving trends of MR/CA research.